Pengembangan Materi Tambahan Bagi Siswa Cepat Belajar Kelas 8 SMP - Hardiantini, Luh Rista; Nitiasih, Putu Kerti; Suputra, Putu Eka Dambayana (Jurnal IKA, 2023)
Fast learners in the class need a variety of learning activities. They are fast in comprehending the material provided by the teacher. Therefore, this study aimed to develop supplementary material for the fast learner in eighth-grade students. The material was developed to facilitate students in learning. Besides, it was an additional activity for the students. This study used the D&D research model proposed by Richey and Klein (2007). This model has four stages: analysis, design, development, and evaluation. In the analysis stage, the researcher analyzed related documents such as the book and syllabus. The process continued by designing a blueprint or draft of the supplementary material. Then, the development of the book started. The researcher considered the needs and the ability of fast learners. Last, the evaluation was conducted to know the quality of the book. Three expert judges evaluated the book, and two teachers evaluated the book. The average score obtained from expert judges and teachers was 149. Thus, the product developed was categorized as "Good" from the experts and teacher. Besides, four users reviewed the book. The average result obtained was 46. Thus, according to users the product was categorized as "Very Good". From the result obtained, the book is suitable as additional material for fast learners.